Shattered Veins Elucidate Brittle Creep Processes in the Deep Slow Slip and Tremor Region. Issue 4 (29th March 2023) - Muñoz‐Montecinos, J.; Angiboust, S.; Garcia‐Casco, A.; Raimondo, T.
Abstract: Deep Slow Slip and Tremors (SSTs) are a combination of transient clusters of tectonic tremors and slow slip associated with extremely elevated fluid pressures. SSTs are thought to reflect a transition from viscous to brittle plate interface rheology and likely exert a first‐order control on megathrust seismicity. Nevertheless, the deformation mechanisms governing the source of SSTs remain elusive. We herein document the occurrence of vein networks precipitated and brecciated within the deep SST region under blueschist‐facies conditions. These lawsonite‐rich vein sets exhibit extensive evidence of brittle deformation and are spatially related to localized, finely milled (cataclastic) shear bands. Petro‐geochemical data reveal that brittle deformation was accompanied by the injection of several ultramafic‐, mafic‐ and metasedimentary‐derived fluid pulses, imprinting characteristic Cr, high field strength elements, and light over heavy rare earth elements positive anomalies in the vein breccias while leaching light rare earth elements from the cataclastic blueschist host. Our results suggest that metamorphic veins represent zones of mechanical anisotropy within the rock volume prone to localized shearing, brittle deformation and episodic injection of externally derived fluids. These networks demonstrate the importance of former vein sets as structural heterogeneities in triggering fluid‐controlled brittle creep events. The combined effects of high pore fluid pressures and rheological heterogeneities in the form of metamorphic veins could trigger the nucleation and propagation of SSTs at the margins of this mechanically anisotropic environment, and thus determine where slip will take place along deep subduction interfaces. Plain Language Summary: The discovery of "slow" earthquakes that occur at such slow velocities that are imperceptible to human senses but can be measured instrumentally has generated a number of questions regarding the rheological behavior of subduction zones. A key approach to gain valuable information about these phenomena is by studying metamorphic rocks that were once buried, and subsequently exhumed, to and from depths at which these slow earthquakes occur. In this paper we study the structures that record the deformation of these rocks. We report a diversity of structures, among which are veins that are made of minerals that behave as rigid objects, while the surrounding rock matrix behaves in a viscous manner. We note that evidence of brittle and shear deformation is found mainly in these veins and in the rock immediately surrounding them. These brittle deformation events would have been triggered by the contrast in mechanical properties between the veins and their host rock, as well as by the injection of fluids at high pressures. These structures exhibit characteristics that can be compatible with some of these slow earthquakes, shedding light on their formation source processes. Key Points: Metamorphic veins are rheological heterogeneities capable of localizing deformation within the rock volume (Ultra)cataclasites and breccias are inferred to have formed at blueschist‐facies conditions; blueschists deformed by brittle and pressure‐solution creep mechanisms Brittle fabrics are associated with the injection of externally derived fluids at depths compatible with slow slips and tremors